The Effects of Trimetazidine on QT-interval Prolongation and Cardiac Hypertrophy in Diabetic Rats - Ramezani-Aliakbari,Fatemeh (2019)
Abstract Background: Trimetazidine (TMZ) is an anti-ischemic drug. In spite of its protective effects on cardiovascular system, there is no scientific study on the usefulness of TMZ treatment for prolonged QT interval and cardiac hypertrophy induced by diabetes. Objectives: To evaluate the effects of TMZ on QT interval prolongation and cardiac hypertrophy in the diabetic rats. Methods: Twenty-four male Sprague-Dawley rats (200-250 g) were randomly assigned into three groups (n = 8) by simple random sampling method. Control (C), diabetic (D), and diabetic administrated with TMZ at 10 mg/kg (T10). TMZ was administrated for 8 weeks. The echocardiogram was recorded before isolating the hearts and transfer to a Langendorff apparatus. Hemodynamic parameters, QT and corrected QT interval (QTc) intervals, heart rate and antioxidant enzymes were measured. The hypertrophy index was calculated. The results were evaluated by one-way ANOVA and paired t-test using SPSS (version 16) and p < 0.05 was regarded as significant. Results: The diabetic rats significantly indicated increased hypertrophy, QT and QTc intervals and decreased Left ventricular systolic pressure (LVSP), Left ventricular developed pressure (LVDP), rate pressure product (RPP), Max dp/dt, and min dp/dt (±dp/dt max), heart rate, superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase in the heart. Treatment with TMZ in the diabetic animals was significantly improved these parameters in comparison to the untreated diabetic group. Conclusions: TMZ improves QTc interval prolongation and cardiac hypertrophy in diabetes.